The Learner's Reading Ethos - Ayu Samma; Muhammad Arpansyah (ISNU Sumatera Utara, 2025)
Reading ethos is a mental attitude and intellectual habit that is very important in the academic world, especially for students majoring in Constitutional Law who are required to understand normative, constitutional, and legal philosophical texts. In the context of academic ethics, reading is not merely a technical activity, but a form of intellectual responsibility towards knowledge. This paper aims to analyze how reading ethos can be a pillar of academic ethics and how it is applied in shaping the character of students who are critical, honest, and have integrity. This study uses a descriptive qualitative approach with data obtained from literature studies and observations of student academic behavior. The results of the analysis show that students with a strong reading ethos tend to have the ability to think systematically, appreciate the scientific work of others, and uphold the value of academic honesty.